Analisis Perwatakan Tokoh dan Konflik Internal Tokoh dalam Novel Me and My Broken Heart Karya Wulanfadi - Senjaya, Yuni; Shomary, Sudirman (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
Not only that, the creation of literary works also leads to high thoughts that are not only formed from mere daydreams. Based on this fact, the author conducted a research with the title "Analysis of Character Characterization and Internal Conflict in the Novel Me And My Broken Heart". The problems in this study are: How is the characterization of the characters and the internal conflict of the characters in the novel Me and My Broken heart by Wulanfadi? The purpose of this study is to describe and analyze the characterization and internal conflict of the characters in the novel Me and MyBroken Heart by Wulanfadi. The theory used in this research refers to the theories of Mana Sikana (2005), Minderop (2010), and Burhan Nurgiyantoro. The data in this research are words and sentences in the novel Me and My Broken Heart by Wulanfadi. This research approach uses a qualitative approach, the method used is descriptive method using hermeneutic techniques and analyzed using content analysis techniques. The results of this study conclude that there are 7 characters, including: Mika, has a jail character, friendly, angry, snappy, witty, brave, talkative, flirtatious, afraid, wise. The internal conflict that occurs is Mika feeling guilty to her best friend for liking Luna.